Vietnamese students learning the semantics of English prepositions - Hung, Bui Phu (Penerbit Universiti Kebangsaan Malaysia, 2017)
Prepositions are significant in sentences because they are used as markers to join words and phrases into a sentence. Teachers usually teach prepositions by providing students with explanations about the usage of prepositions and then gives examples as illustrations. These examples are often accompanied by vivid pictures. This method, however, does not provide students information on how to analyze the different senses of prepositions. This current study, thus, aims to explore the effectiveness and students’ opinions of new pedagogical instructions on ten English prepositions, namely above, among, at, behind, beside, between, in, in front of, on and under. The research design involved a quasi-experimental design adopting pretest-posttest between-group research. Out of 95 students who volunteered to participate in the study, 38 participants were selected. They were divided into two groups for the new cognitive linguistic approach and traditional instructions. Pretest and posttest were used to discover the participants’ improvements. The participants’ opinions of the cognitive treatment were also investigated. The findings illustrate that the group that was treated with CL-based instructions outperformed the traditional group in the posttest although they gained a comparable mean score in the pretest. Most participants also provided positive responses to the new treatment. The findings suggests that cognitive treatment could be employed to assist students in improving their understanding and retaining the metaphorical meanings of the prepositions.